ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN DALAM MEMBELI MINYAK GORENG MEREK SUNCO - wulan, wulan kuara (Agriprimatech, 2020)
ABSTRACT "Analysis of consumer purchasing decisions in buying Sunco cooking oil (Case study: Women of Bebesen sub-district, Central Aceh district)" This research was guided by Mrs. Myrna Pratiwi Nasution, SP, M P. This study aims to analyze consumer purchasing decisions in buying Sunco cooking oil, This research was conducted in Bebesen sub-district, Central Aceh district, the respondents used were 100 women, the community of Bebesen sub-district, Central Aceh district. Then the test tool used in this study is multiple linear regression using the SPSS 24 software. The results of this study indicate that the product has a significant effect on the decision to purchase Sunco cooking oil, the promotion has a significant effect on the decision to purchase Sunco cooking oil, the price has no significant effect on the purchase decision for Sunco cooking oil, and the place has no significant effect on the decision to purchase Sunco cooking oil. So products and promotions have a significant effect on Sunco cooking oil.